Implementasi Sistem Informasi Terintegrasi Berbasis Daerah untuk Pemetaan Kinerja dan Pengelolaan Sumber Daya Organisasi IKBMY DIY: Implementation of a Region-based Integrated Information System for Performance Mapping and Resource Management of IKBMY DIY - Zaidir Zaidir; Veronika Wiratna Sujarweni; Erizal Erizal; Indra Listiawan; Fairuz Az Zahra Kamila Nugraha (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Region-based community organizations frequently face challenges in performance mapping and data management due to manual, fragmented administrative practices, as experienced by Ikatan Keluarga Besar Minangkabau Yogyakarta (IKBMY DIY). This community service initiative aims to implement a region-based integrated information system to support systematic and sustainable performance mapping and organizational resource management. The implementation method includes participatory needs assessment, system development tailored to organizational requirements, training and mentoring for administrators, and post-implementation evaluation using both quantitative and qualitative approaches. The results demonstrate improved administrative orderliness, centralized data availability, and enhanced reporting efficiency. Post-training evaluation involving 30 participants indicates high user acceptance and satisfaction, particularly regarding ease of use and feature relevance. Overall, this initiative strengthens organizational capacity and promotes more transparent, accountable, and sustainable management practices, with potential applicability to similar community-based organizations.